Resilience of Participatory Communication Adolescent Community Communities in the Prevention of Child Marriage in Sukabumi - Yessi Sri Utami (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
This research has an urgency that participatory communication resilience can be formed in communities with young ages, namely adolescents who are members of adolescent communities. This research focuses on how resilience is formed in adolescent communities to prevent child marriage in Sukabumi Regency to improve the ability of adolescents and advocate for vulnerable peers trapped in child marriage. This research uses qualitative research methods with a case study approach to explore the experiences of adolescent members of 5 regional children's forums in Sukabumi as research subjects who actively participate in the prevention of child marriage through the Yes I Do program. The results showed that participatory communication of child communities in preventing child marriage in formal and informal peers showed the collaboration of child communities with diverse cross-communities (heteroglacia). In addition to heteroglacia, Wabinar Activities are open dialogue and sharing experiences and knowledge with peers (dialogue) Movie watching and business class activities are a process to unite some of the differences that exist into an understanding about the impact of child marriage (polypony). Youth Camp and Watch Together activities filled by the children's community are a form of fun participatory communication (carnival). The children's community builds meaning, persistence, self-confidence, patience, independence or what is referred to as peer resilience with peer education activities. Resilience in adolescents who are vulnerable to being trapped in child marriage is an important period and affects the basis of adulthood, individual changes and life development.